Pengaruh Kualitas Layanan Dan Kesadaran Merek Terhadap Minat Konsumen Serambi Dana Koperasi Di Surabaya - Sufyandi Sufyandi; Muhammad Anang Firmansyah; Asyidatur Rosmaniar (BALANCE: Economic, Business, Management and Accounting Journal, 2019)
ABSTRACT  The aim of this research are (1) to analyze the role of KPU in the implementation of internal This research was conducted to find out how much influence of the quality of service, and brand awareness, on the consumers’ interest of Serambi dana koperasi in Surabaya. This type of research is pure descriptive research or survey. The population in this research are customers of Serambi dana koperasi who are 134 permanent members. The results of this research indicate that service quality partially influences consumer interest in Serambi dana koperasi Surabaya, Then it can be concluded that the brand awareness variable has a significant effect on the consumer interest variable partially. From the results of the above calculations it can be concluded that the effect of service quality and brand awareness on consumer interest in the Serambi dana koperasi Surabaya, it is known that both (service) variable service quality (X1), and brand awareness (X2) have a significant effect on variable consumer interest (Y).Keywords                   : Service Quality, brand awareness, consumer interest, serambi danaCorrespondence to       : anangfirmansyah.61@gmail.com  ABSTRAK  Penelitian ini dilakukan untuk mengetahui seberapa besar pengaruh kualitas layanan, dan kesadaran merek, terhadap minat konsumen serambi dana, koperasi di Surabaya. Jenis penelitian ini adalah penelitian deskriptif murni atau survey, Populasi dalam penelitian  ini adalah  nasabah koperasi serambi dana Surabaya yang menjadi anggota tetap sebanyak 134 nasabah. Hasil penelitian ini menunjukkan bahwa kualitas Layanan secara parsial berpengaruh terhadap minat konsumen serambi dana koperasi  di Surabaya, dimana  setelah dilakukan hasil uji hipotesis (Uji t) menunjukkan bahwa variabel kualitas layanan (X1) dan variabel kesadaran merek (X2)  berpengaruh terhadap variabel minat konsumen.Kata Kunci       : Kualitas Layanan, kesadaran merek, minat konsumen, serambi danaKorespondensi : anangfirmansyah.61@gmail.com